Label Retaining and Stem Cell Marker Expression in the Developing Rat Urinary Bladder - Zhang, Haiyang (2011)
OBJECTIVES: Tissue resident stem cells are believed to exist in most tissues, and their identification is commonly done by a combination of immunostaining for putative stem cell markers and the label-retaining cell (LRC) strategy. In the present study we employed these approaches to identify potential stem cells in the urinary bladder. METHODS: Newborn rats were intraperitoneally injected with 5-ethynyl-2-deoxyuridine (EdU), and their bladders harvested at four different time points afterward. The bladders were processed for EdU staining and immunofluorescence staining for stem cell markers Lgr5, CD34, SSEA-1, and c-kit. EdU-positive cells were counted and co-localization with stem cell markers determined. RESULTS: At day one post-EdU injection, 1804.0 ± 227.7 bladder cells were labeled in each cross section. As time increased, fewer bladders remained labeled, dropping to 236.5±53.0 cells per field. In the 1-day bladders, 27.5±4.9% of the epithelial cells were labeled as compared to 12.1±2.8% in the detrusor. The labeling rates in these two tissue compartments gradually equalized, reaching at approximately 5.5% in the 8-week samples. Distribution of LRC was random, without preferential labeling of basal cells. Lgr5 and SSEA-1 were detectable in the urothelium; CD34 and c-kit in the lamina propria and detrusor. Approximately 30 to 40% of c-kit-positive cells were EdU-positive. CONCLUSIONS: Labeling of bladder cells by EdU occurred randomly, and label retaining was not associated with expression of Lgr5, CD34, or SSEA-1. The strong association between label retaining and c-kit expression appears to relate to interstitial cells of Cajal (ICCs), not stem cells.